Towards a theory of entrepreneurial teams - Harper, David A. (Journal of Business Venturing, 2008)
This article examines the role of entrepreneurial teams in processes of entrepreneurial discovery. It addresses two main questions. The first investigates the implications of economic theory for the possibility of team entrepreneurship. Because leading economic theories focus almost exclusively upon individual decision-makers, we propose a broader notion of entrepreneurship that includes enterprising teams as well as individuals. We define entrepreneurship as a profit-seeking problem-solving process that takes place under conditions of structural uncertainty. The second question examines the conditions that are conducive to joint entrepreneurial action and the formation of entrepreneurial teams. We suggest that bounded structural uncertainty and perceived strong interdependence arising from common interest can jointly “prime” team entrepreneurship.